The art of political manipulation - Riker, William H. (New Haven Yale University Press, 1986)
In twelve engrossing stories whose protagonists range from Pliny the Younger to Abraham Lincoln to Adam Clayton Powell, a noted political scientist and game theorist demonstrates how some of our heroes as well as ordinary folk have manipulated their opponents in order to win political advantage.
Keywords: Political leadership